Trends in Digitalization and Cultural Identity: A Bibliometric Study on Local Traditions in the Digital Era - Judijanto, Loso; Nurjani, Ni Putu Suda; Nurmiati, Ai Siti; Lubis, Arief Fahmi (Westscience Press, 2024)
This study explores the interplay between digitalization and cultural identity with a focus on local traditions in the digital era, using a bibliometric approach. By analyzing academic publications from key databases, the research identifies trends, thematic clusters, and emerging areas of interest in this interdisciplinary field. Results indicate that